Evaluation of Corrosion Critical Variables of 304 Stainless Steel by Delay Time of Acoustic Emission - Wu, Kaige; Jung, Woo-Sang; Byeon, Jai-Won (JAPAN INST METALS, 2015)
In this work, a new experimental setup for acoustic emission (AE) monitoring was designed to study the process of pitting corrosion of 304 stainless steel. Two AE sensors were employed in the present setup to investigate the AE behaviors of the pitting process in the working electrode and the hydrogen bubbles on the counter electrode separately and simultaneously. The AE signals from hydrogen bubbles on the counter electrode started to be detected with a delay time (defined as Delta t(1)) after the pitting potential was reached. Then the AE signals from the pitting process were detected after another delay time (defined as Delta t(2)). The parameters of Delta t(1) and Delta t(2) generally decreased with the increase in sodium chloride concentration. Another parameter, Delta t(3), was defined as the time difference between the first detections of the AE signals from hydrogen bubbles on the counter electrode and the pitting process on the working electrode. The AE signal-derived parameter, Delta t(3), decreased linearly with the increasing concentration of sodium chloride. Furthermore, the value of Delta t(3) was directly proportional to open circuit potential (E-OC) and pitting potential (E-P) of 304 stainless steel, respectively. These correlations imply that the more easily pitting corrosion occurs, the lower the value of Delta t(3) would be and vice versa. The AE-derived time-delay parameter reflecting the pitting corrosion process can offer an alternative idea for evaluation of the corrosion critical variables and the pitting corrosion resistance.
Keywords: MONITORING PITTING CORROSION; AUSTENITIC STAINLESS-STEELS; INITIATION; PASSIVITY; BREAKDOWN; METALS; MEDIA